TRANSETHOSOMES FOR ENHANCED TRANSDERMAL DELIVERY OF METHOTREXATE AGAINST RHEUMATOID ARTHRITIS: FORMULATION, OPTIMISATION AND CHARACTERISATION - PRATIKSHA N., POOJARI; PRIYA, SNEH; SANJANA; KHANDIGE, PRASANNA SHAMA (International Journal of Applied Pharmaceutics, 2024)
Objective: The study aimed to develop and optimise Methotrexate (MTX)-loaded Transethosomal Film-Forming Gel (TE FFG) for transdermal delivery to treat rheumatoid arthritis while alleviating the side associated with oral administration. Methods: The Transethosomes (TE) were prepared using the thin film hydration technique and incorporated into an FFG using chitosan. The Box-Behnken Design method was used to analyse the influence of independent variables such as the concentration of soya lecithin, surfactant, and ethanol on parameters including vesicle size, PDI (Polydispersity Index), zeta potential, and entrapment efficiency. The optimised transethosomal suspension was incorporated into the FFG using 3% chitosan and other excipients. In vitro drug release and ex vivo skin permeation of FFG were performed using Franz diffusion cells. Results: The vesicle size, PDI, zeta potential and entrapment efficiency of the optimised formulation of TE were 110.3 nm, 0.352,-14.4 mV and 49.36%, respectively. The Transmission Electron Microscopy (TEM) image showed that the vesicles were uniform and spherical. The in vitro drug release study was higher for Conventional (CL) FFG) than TE FFG and the drug release mechanism was fitted into the Higuchi model. The permeation was higher for TE FFG, with the steady-state flux being 1.55 times greater than the CL FFG. The skin irritation test on Wistar rats revealed no indication of irritation on the skin. The histopathology examination showed a significant reduction in the inflammatory cells in the treated group. Conclusion: Therefore, the results concluded that the formulated MTX-loaded TE FFG could be a potentially promising substitute for the oral delivery of methotrexate